Mechanical analysis of the roundhouse kick according to height and distance in taekwondo - Estevan, I.; Falcó, C. (Biology of Sport, 2013)
Anthropometric characteristics of athletes are considered to be an important determinant of success in sport. The aim of the present study was to compare several anthropometric parameters and subjective characteristics of professional elite triathletes with anthropometric profiles of professional cyclists and sportive students. In total 93 volunteers (21 male and female triathletes, 26 male cyclists and as a control group 46 male and female students) participated in this study. Eight different anthropometric parameters were measured and a five-page questionnaire containing 35 general questions had to be completed. Interestingly, there were no significant differences between the arm span, the lengths of the lower limb and the circumference of waist and hip between male triathletes and cyclists. As expected, the athletes had significantly lower heart rates and lower weights as compared to the controls. Further results showed that male cyclists had a higher BMI, larger thighs and were taller as compared to the male triathletes. The present study could not evaluate specific anthropometric characteristics as predictive factors of performance in elite athletes. Thus, individual successful performance is linked to discipline and talent rather than to a specific anthropometric profile.